Fluorinated β‐Ketoiminate Zinc Complexes: Synthesis, Structure and Catalytic Activity in Ring Opening Polymerization of Lactide. Issue 18 (1st June 2021) - Ghosh, Swarup; Huse, Kevin; Wölper, Christoph; Tjaberings, Alexander; Gröschel, André H.; Schulz, Stephan
Abstract: Complexes LZnR (L=C6 F5 NC(CF3 )C(H)C(CF3 )O; R=Me 1 ; Et 2 ) and L2 Zn(thf)2 (3 ) were synthesized and analyzed by NMR ( 1 H, 13 C, 19 F) and IR spectroscopy, elemental analysis, and single crystal X‐ray diffraction. Complexes 1 and 2 are dinuclear in the solid state but monomeric in toluene solution according to diffusion‐ordered spectroscopy (DOSY‐NMR). They showed poor activity in the ring opening polymerization (ROP) of lactide (LA) but moderate activity in the presence of benzyl alcohol (BnOH), yielding polymers with high number average molecular weight ( M n ) and moderately controlled molecular weight distribution (PDI). Homonuclear‐decoupled 1 H NMR analysis of polylactic acid (PLA) obtained from rac ‐LA showed isotactic enrichment of the polymer microstructure, and kinetic studies of the ROP of L‐ LA with complex 2 showed a first order dependence of the monomer concentration. Analyses of low molecular weight polymers by 1 H NMR and MALDI‐ToF mass spectrometry demonstrated the coordination‐insertion mechanism (CIM). Abstract :